Successful citizen science tools to monitor animal populations require innovation and communication: SealSpotter as a case study - Puskic, Peter S.; Holmberg, Ross; McIntosh, Rebecca R. (Frontiers in Conservation Science, 2024)
In rapidly changing ocean systems, there is a dual need to engage and educate community members and carry out rapid data acquisition. There is a body of evidence to support community or citizen science projects as successful vehicles for achieving these goals, with a particular need to increase global ocean literacy. The online SealSpotter program is a citizen science initiative aimed at monitoring trends in Australian fur seal (Arctocephalus pusillus doriferus) populations and connecting people to the marine environment. Here we present the findings of five years of monitoring of fur seals using drone surveys counted by citizen scientists via SealSpotter. Over five years, global participants from 23 countries were engaged in counting seals with a focus on the annual breeding season and pup abundance, with an average of 13,479 images and 171,137 seals counted per year. SealSpotter participants presented more conservative (lower) counts than expert counts, however both groups detected similar trends in abundance, emphasizing success of the project aims that included obtaining a precise index of pup abundance; ultimately a more achievable goal than accuracy due to the difficulties in measuring absolute abundance. We reflect on SealSpotter's accomplishments and highlight the potential for marine citizen science programs as important tools for addressing global ocean literacy needs. The SealSpotter program contributes to our understanding of marine ecosystems through a simple but effective citizen science program. Unofficial change and ideally require monitoring, efficient methods to observe changes and forecast future scenarios are needed (Chapin et al., 2010).